Acute Gastric Dilatation Resulting in Gastric Emphysema Following Postpartum Hemorrhage. (24th April 2012) - Khan, Suhail Aslam; Boko, Edmond; Khookhar, Haseeb Anwar; Woods, Sheila; Nasr, A. H.
Abstract : Acute gastric dilatation is a rare entity, with varying aetiologies the majority of which are benign. Delay in diagnosis and treatment could result in sequelae such as gastric emphysema (pneumatosis), emphysematous gastritis, gangrene, and perforation. Gastric emphysema as a result of a benign nongangrenous condition such as gastroparesis, adynamic ileus can be successfully managed conservatively. Here, we present an interesting case of acute gastric dilatation resulting in gastric emphysema following massive postpartum hemorrhage.